The Effects of Anxiety and Emotional Intelligence on The Mathematic Learning Outcomes of Fifth Grade Students - Ni Komang Reza Cahyani; I Gusti Agung Ayu Wulandari (Universitas Pendidikan Ganesha, 2021)
Students experience very high anxiety, so it impacts the difficulty of digesting and understanding mathematics learning materials. It causes low Mathematics learning outcomes. This study analyzes the effect of anxiety and emotional intelligence on fifth-grade elementary school students' mathematics learning outcomes. This study was an